Adapting automated instrumentation for high‐throughput calcium isotope measurements by multi‐collector inductively coupled plasma mass spectrometry. (7th February 2022) - Razionale, Dan; Bryant, Roger N.; Blättler, Clara L.
Abstract : Rationale: Large, efficiently generated datasets of calcium isotope ratios offer tremendous utility in an increasing number of scientific disciplines. Modern analytical capabilities in mass spectrometry present unique challenges to previously established sample preparation techniques, the extent of which must be thoroughly examined before these data are interpreted and reported. This study addresses key methodological challenges in the determination of calcium isotopes using state‐of‐the‐art, commercially available instruments. Methods: Automated ion chromatography was used to isolate calcium from carbonate‐ and seawater‐like samples prior to analysis by multi‐collector inductively coupled plasma mass spectrometry (MC‐ICP‐MS). A new, membrane‐bearing desolvator (Apex‐Ω) is implemented and achieves enhanced sensitivity, yet necessitates an update to established sample preparation techniques due to previously unobserved matrix effects. Performance of this method was assessed through analyses of multiple standard reference materials (SRM 915b, USGS EN‐1, and seawater) and several in‐house standards using a Neptune MC‐ICP‐MS instrument. Results: The enhanced sensitivity afforded by the Apex‐Ω also yields pronounced matrix effects during mass spectrometry, resulting specifically from heightened sample Na and Sr content and deviations in sample [Ca] from their bracketing standards. While the latter can be addressed by a concentration correction, the first two matrix effects are mitigated using a modified chromatography technique that implements unique rinsing protocols. Conclusions: This precise (0.14‰ 2 σ ), high‐throughput method is very reproducible for small sample amounts and, at optimal efficiency, can generate approximately 140 sample δ 44/40 Ca values per week with 5 h of in‐person effort per day. Documented matrix effects are successfully mitigated through corrections and modified chromatographic techniques. Additionally, this method may be permuted to accommodate most major cations.